Analysis of NGINX Static Content Delivery on the Performance of a Docker-based Photo Gallery Backend - Itsna Nur Hamida; Masy Ari Ulinuha; Hery Mustofa; Khothibul Umam (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2026)
Photo studio websites typically present large volumes of multimedia content through photo gallery modules. In many implementations, this content is served dynamically by the application backend, which can increase processing load and degrade system performance. This study analyzes the impact of static content delivery using NGINX on the performance of a Docker-based photo gallery backend. A quantitative experimental method was applied by comparing two scenarios: dynamic content delivery without NGINX and static content delivery using NGINX. The experiments were conducted using Apache Benchmark with identical request and concurrency parameters, accompanied by monitoring of backend resource utilization. The results show that dynamic delivery produces lower throughput (463.78 requests per second) and higher response time (108.27 ms), along with significant backend CPU usage. In contrast, the use of NGINX increases throughput to 1105.25 requests per second, reduces response time to 45.33 ms, and significantly lowers backend CPU and memory consumption. These findings demonstrate that separating static and dynamic content delivery using NGINX is effective in improving backend performance in Docker-based photo gallery applications.